BMP-dependent serosa and amnion specification in the scuttle fly Megaselia abdita - Rafiqi, Abdul Matteen; Lemke, Steffen (Development, 2012)
Skip to Next Section Bone morphogenetic protein (BMP) signaling is an essential factor in dorsoventral patterning of animal embryos but how BMP signaling evolved with fundamental changes in dorsoventral tissue differentiation is unclear. Flies experienced an evolutionary reduction of extra-embryonic tissue types from two (amniotic and serosal tissue) to one (amnionserosal tissue). BMP-dependent amnioserosa specification has been studied in Drosophila melanogaster. However, the mechanisms of serosal and amniotic tissue specification in less diverged flies remain unknown. To better understand potential evolutionary links between BMP signaling and extra-embryonic tissue specification, we examined the activity profile and function of BMP signaling in serosa and amnion patterning of the scuttle fly Megaselia abdita (Phoridae) and compared the BMP activity profiles between M. abdita and D. melanogaster. In blastoderm embryos of both species, BMP activity peaked at the dorsal midline. However, at the beginning of gastrulation, peak BMP activity in M. abdita shifted towards prospective amnion tissue. This transition correlated with the first signs of amnion differentiation laterally adjacent to the serosa anlage. Marker-assisted analysis of six BMP signaling components (dpp, gbb, scw, tkv, sax, sog) by RNA interference revealed that both serosa and amnion specification of M. abdita are dependent on BMP activity. Conversely, BMP gain-of-function experiments caused sharpened expression boundaries of extra-embryonic target genes indicative of positive feedback. We propose that changes in the BMP activity profile at the beginning of gastrulation might have contributed to the reduction of extra-embryonic tissue types during the radiation of cyclorrhaphan flies.